Study on formation of nitrated polycyclic aromatic hydrocarbons from different roasting condition in coffee - Ko, Jae-Hyung (J Food Sci Technol, 2018)
Nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) are organic, carcinogenic and mutagenic compounds that originate from the reaction of PAHs with NO(x) and OH radicals. In this study, an analytical method was developed, for the determination of seven nitro-PAHs and the method was applied to quantify the nitro-PAHs, in coffee model systems, prepared with coffee beans produced from three distinct locations and under various roasting conditions. Also, experiments were performed to study the effect of adding various amino acids on the formation of nitro-PAHs. The free radicals produced, were quantified by electron spin resonance (ESR), to assess their correlation with the formed nitro-PAHs. After extraction and cleanup, the nitro-PAHs in coffee were analyzed by gas chromatography/mass selective detection. In all heated coffee model systems, the addition of the amino acids, significantly increased the nitro-PAHs compared to the control. The ESR results were consistent with previous outcomes on the formation of nitro-PAHs.